Elucidation of the biochemical basis for a clinical drug–drug interaction between atorvastatin and 5-(N-(4-((4-ethylbenzyl)thio)phenyl)sulfamoyl)-2-methyl benzoic acid (CP-778 875), a subtype selective agonist of the peroxisome proliferator-activated receptor alpha. (November 2013) - Kalgutkar, Amit S.; Chen, Danny; Varma, Manthena V.; Feng, Bo; Terra, Steven G.; Scialis, Renato J.; Rotter, Charles J.; Frederick, Kosea S.; West, Mark A.; Goosen, Theunis C.; Gosset, James R.; Walsky, Robert L.; et al.
Abstract 1. <?ri?>5-(N-(4-((4-ethylbenzyl)thio)phenyl)sulfamoyl)-2-methyl benzoic acid (CP-778 875), an agonist of the peroxisome proliferator-activated receptor alpha, has been evaluated in the clinic to treat dyslipidemia and type 2 diabetes mellitus. Herein, we investigate the effect of CP-778 875 on the pharmacokinetics of atorvastatin acid and its metabolites in humans. 2. <?ri?>The study incorporated a fixed-sequence design conducted in two groups. Group A was designed to estimate the effects of multiple doses of CP-778 875 on the single dose pharmacokinetics of atorvastatin. Subjects in group A (n = 26) received atorvastatin (40 mg) on days 1 and 9 and CP-778 875 (1.0 mg QD) on days 5–12. Group B was designed to examine the effects of multiple doses of atorvastatin on the single dose pharmacokinetics of CP-778 875. Subjects in group B (n = 29) received CP-778 875 (0.3 mg) on days 1 and 9 and atorvastatin (40 mg QD) on days 5–12. 3. <?ri?>Mean maximum serum concentration (Cmax) and area under the curve of atorvastatin were increased by 45% and 20%, respectively, upon co-administration with CP-778 875. Statistically significant increases in the systemic exposure of ortho- and para-hydroxyatorvastatin were also observed upon concomitant dosing with CP-778 875. CP-778 875 pharmacokinetics, however, were not impacted upon concomitant dosing with atorvastatin. 4. <?ri?>Inhibition of organic anion transporting polypeptide 1B1 by CP-778 875 (IC50 = 2.14 ±<!-- -->0.40 μM) could be the dominant cause of the pharmacokinetic interaction as CP-778 875 did not exhibit significant inhibition of cytochrome P450 3A4/3A5, multidrug resistant protein 1 or breast cancer resistant protein, which are also involved in the hepatobiliary disposition of atorvastatin.